Assessment of Morphological Variability in Gum karaya (Sterculia urens Roxb.) from Tropical Deciduous Forest of Madhya Pradesh - Mohammad, Naseer (Indian Forester, 2024)
The study presents a comprehensive analysis of morphometric variability in Sterculia urens populations from Tropical deciduous forest of central India. In the overall studied populations, tree height ranged from 1.9 m to 48 m, with an average of 8.68 m and a coefficient of variability (CV) of 48%. Different forest divisions exhibited varying heights, with Seoni having the highest average height (15.02 m). Clear bole height ranged from 0.5 m to 9.0 m, with a 54% CV. Girth at breast height (GBH) showed the highest CV at 63%, ranging from 10.0 cm to 416.0 cm, with an average of 127.65 cm. The number of branches per plant ranged from 2 to 15, with an average of 4.66 branches. Agglomerative hierarchical clustering was conducted based on all morphological traits, revealing that most sampled locations grouped into a single cluster with Seoni and Jhabua-Dhar as outliers. The cluster analysis grouped most sampled locations into a single cluster, with two outliers (Seoni and Jhabua-Dhar). Measures of clustering quality, such as the cophenetic correlation coefficient (0.93) and delta (0.14), suggested that the clustering was useful. The analysis reveals that most populations have similar variations, suggesting limited morphological sub-divisions. The study emphasizes the need for combining molecular markers with morphological traits for a more comprehensive assessment of population structures in S. urens.